2011
DOI: 10.4028/www.scientific.net/amr.332-334.23
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Application of Alkalophilic Strains for Biological Scouring of Flax Rove

Abstract: To achieve bio-scouring or biological degumming of the flax roving, an alkalophilic strain was screened from the rotten wrack around Zhoushan archipelago sea area. Determination of enzyme activity showed that the activities of petinase and xylanase were obtained, and enzyme activities are stable under 50°C and at pH values in the range of 6.5 to 9.0. It was utilized to scour the flax roving under alkaline conditions, and the result showed that the strain had a good characteristic of scouring, and less strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, the influence of each component on the fiber property was not discussed. Ding 19 and Guo 20 tried to semi-degum a flax roving with a complex enzyme of pectinase and hemicellulose, and the results showed that super short fiber length or super high density would be obtained under some reaction conditions, but the key factors influencing the fiber length and density were not discussed. However, the influence of hemicellulose, pectin and lignin on the fiber property and the regulation and priority of the degradation and dissolution of the gummy materials remained unclear.…”
mentioning
confidence: 99%
“…However, the influence of each component on the fiber property was not discussed. Ding 19 and Guo 20 tried to semi-degum a flax roving with a complex enzyme of pectinase and hemicellulose, and the results showed that super short fiber length or super high density would be obtained under some reaction conditions, but the key factors influencing the fiber length and density were not discussed. However, the influence of hemicellulose, pectin and lignin on the fiber property and the regulation and priority of the degradation and dissolution of the gummy materials remained unclear.…”
mentioning
confidence: 99%